2018
DOI: 10.1016/j.wem.2018.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Use and Attitudes Toward Performance-Enhancing Drugs in Ultramarathon Running

Abstract: Introduction-The use of performance enhancing drugs (PEDs) has been reported in several sports. There have been no peer-reviewed articles on the use of PEDs in ultramarathon running. This study was to examine the use of PEDs in ultramarathon running and to identify attitudes and beliefs about the usage of PEDs in the sport. Methods-An online survey was developed. The survey was distributed to potential participants through Ultrasignup and the Western States Endurance Run Facebook sites. The survey included 9 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…The strength of this study is the online recruitment of a relatively large sample in a short amount of time. Community-based adult athletes have been infrequently studied with respect to cannabis use, patterns of use, or subjective effects to cannabis (Campian et al 2018). Most studies of cannabis use in athletes have been mainly in adolescents, university athletes, and elite athletes (Ware et al 2018;Buckman et al 2011;Peretti-Watel et al 2003a).…”
Section: Discussionmentioning
confidence: 99%
“…The strength of this study is the online recruitment of a relatively large sample in a short amount of time. Community-based adult athletes have been infrequently studied with respect to cannabis use, patterns of use, or subjective effects to cannabis (Campian et al 2018). Most studies of cannabis use in athletes have been mainly in adolescents, university athletes, and elite athletes (Ware et al 2018;Buckman et al 2011;Peretti-Watel et al 2003a).…”
Section: Discussionmentioning
confidence: 99%
“…A complete overview over the bias check is presented in Supplementary material 1: Table H. Only three studies were identified for selective reporting (Candela et al, 2014;Desalegn et al, 2016;Soltanabadi et al, 2015), just like only seven studies indicated high risk for correlation biases (Campian et al, 2018;Kavussanu et al, 2016;Mudrak et al, 2018;Nicholls et al, 2019b;Ogama et al, 2019;Sukys &Karanauskiene, 2020 andWang et al, 2020). High risk for socially desired responding style was identified in the vast majority of the studies.…”
Section: Bias Assessment Within Studiesmentioning
confidence: 99%
“…Furthermore, doping past-year prevalence estimates of 6.5% ( Molero et al, 2017 ) and 8.2% ( Stubbe et al, 2014 ) as well as lifetime prevalence estimates of 12.5% ( Simon et al, 2006 ) and 14.0% ( Mooney et al, 2017 ) are reported in fitness center members. For recreational endurance athletes, prevalence estimates for doping of 8.1% ( Locquet et al, 2017 ) and 8.4% ( Campian et al, 2018 ) are reported.…”
Section: Introductionmentioning
confidence: 99%